“PASCA LISAN”, A DADAIST FILM WITH TRISIKON - Sito Fossy Biosa; Waret Khunacharoensap (ARTISTIC : International Journal of Creation and Innovation, 2022)
Time-based art, often known as dynamic art, is becoming increasingly popular since the artsy community finds realistic action movies monotonous. In this respect, the Dadaist Film movement is crucial as a part of the dynamics of the non- compartmentalized art. The intimacy of the artistic production and manipulation process of the Dada movement encouraged me to apply the TRISIKON (Three Situations and Conditions) idea to make the Dada movement-inspired film "Pasca Lisan." The Dadaist movie "Pasca Lisan" used the idea of TRISIKON as a way of speaking to depict resistance to terrorist acts. Documentary footage gave the impression that what the camera was capturing actually happened; imaginative animation added the expression and impression effects; and live-action produced absurd, biased, and multi-interpreted dramatic scenes. Additionally, this movie was a picture of art and cross-disciplinary lines that worked together to reveal original and novel concepts, or perhaps things that dared to be referred to as "new."